تقويم مستوى جودة الكتب المدرسية في مرحلة التعليم الأساسي (الحلقة الثانية) وفق المعايير العالمية"دراسة ميدانية في مدينة اللاذقية" - طيوب محمود; درويش رمضان; حسين محمود حسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن ضرورة التقويم باستخدام المعايير العالمية وتطوير المناهج في ضوئها يعد أنموذجاً لضمان الجودة وإدارتها من حيث تحسين المدخلات و العمليات للوصول إلى مخرجات أكثر كفاءة, لذلك تعد هذه المعايير أساس للحكم على الجودة. يتناول البحث الحالي تقويم مستوى جودة الكتب المدرسية في مرحلة التعليم الأساسي (الحلقة الثانية) وفق المعايير العالمية من خلال تصميم استبانة وجهت إلى عينة من المعلمين في هذه المرحلة وتتضمن المحاور التالية: إعداد الكتب وتأليفها, الأساس السيكولوجي والتربوي للكتاب, المادة العلمية للكتاب, الأنشطة والأساليب التعليمية, أساليب تقويم التلاميذ, لغة الكتاب وإخراجه, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: -تتوافق الكتب المدرسية مع المعايير العالمية للجودة بدرجة تتراوح بين المتوسط والجيد في معظمها سواء من حيث إعداد الكتاب, ومادته العلمية, والأنشطة والأساليب, وأساليب التقويم, ولغة وإخراج الكتاب. - توجد فروق ذات دلالة إحصائية بين متوسطات تقديرات أفراد العينة لمدى توافق الكتب المدرسية مع المعايير العالمية للجودة تعزى إلى متغير الخبرة في التدريس. - لا توجد فروق ذات دلالة إحصائية بين متوسطات تقديرات أفراد العينة لمدى توافق الكتب المدرسية مع المعايير العالمية للجودة تعزى إلى متغير الاختصاص. The necessity of Evaluation by using the universal standards and developing of the curricula on the light of this evaluation, is considered a modal to keep the quality and its administration concerning improving the inputs and all processes that lead to better outputs in competency, for this reason these standards are considered the principle of the judgment on the quality. This research deals with the evaluation of the level of the quality of school standards by using a questionnaire applied on the teachers of this stage, it contained these aspects: Preparing the school book and its composing , the psychological and educational principle of the school book , the scientific material of the book , the activities and methods , the methods of evaluation , the language of the book and its designing . After studying and analyses the results were as the following: The school books matches with the universal standards of the quality in a degree which arranged between the medium and the good as a whole , concerning the preparing of the book , its scientific material activities and methods , methods of evaluation and the language and the designing of the school book. There are significant statistical differences between the means of individuals ’ assessments of the sample concerning matching of the school books with the universal standards of the quality in favor of the variable of experience in teaching . There are no significant statistical differences between the means of individuals ’ assessments of the sample concerning matching the school books with the universal standards of the quality, in favor of the variable of specialization .